A new freshwater shrimp species of the genus Palaemon Weber, 1795 (Decapoda: Caridea: Palaemonidae) from northeastern Japan - Katogi, Yuichi; Chiba, Susumu; Yokoyama, Katsuhide; Hatakeyama, Makoto; Shirai, Shigeru; Komai, Tomoyuki (Zootaxa, 2019)
The palaemonid shrimp genus Palaemon Weber 1795 is currently represented by 87 species worldwide, of which 36 species inhabit freshwater environments. In this study, we describe a new species of the genus, P. septemtrionalis, primarily based on material collected from rivers in Miyagi Prefecture, Tohoku District, northeastern Japan. The present new species is morphologically and genetically close to Palaemon paucidens De Haan, 1841, but it is morphologically distinguishable from the latter by the chela of the pereopod 2 being longer than the carpus (versus shorter than the carpus in P. paucidens) and the possession of a low, laminar convexity on the flexor margin of the pereopod 3 dactylus just proximal to the base of the unguis (such a laminar structure is absent in P. paucidens). Comparison of partial sequences of the mitochondrial 16S rRNA gene supports the recognition of the new species. Examination of museum collections and a BLAST search on GenBank revealed that the geographical range of the new species includes the Sea of Japan side ranging from Hokkaido to Hyogo Prefecture and the Pacific side ranging from Aomori to Miyagi Prefecture. An identification key to the 13 Japanese species of the genus is presented.